CLR - Ken Litkowski (Proceedings of the 4th International Workshop on Semantic Evaluations - SemEval '07, 2007)
Background Few long-term studies compare tooth- and implant-supported fixed dental prostheses (FDPs) in the posterior region. Objectives To compare the 5- and 10-year survival and complication outcomes of tooth- and implant-supported FDPs and to assess patient-reported effects. Material and methods This retrospective multicenter clinical study investigates patients treated with 3-5 units tooth-supported fixed dental prostheses (TSFDPs) and 1-4 units implant-supported FDPs in the posterior region at two specialist dental clinics (2009-2019) using clinical and radiographical examinations and Oral Health Impact Profile-14 (OHIP-14). Survival, biological, and technical complications as well as patient-reported effects were recorded. Results A total of 180 patients with 238 FDPs: 113 TSFDPs, 71 implant-supported crowns (ISCs), and 54 implant-supported fixed partial prostheses (ISFPPs) were examined after a mean follow-up of 10 years. The 5-year cumulative survival rate for TSFDPs and implant-supported FDPs was 98% (p = 0.71). The 10-year cumulative survival rates were 94% for TSFDPs and 93% for implant-supported FDPs (p = 0.87). Eight TSFDPs, three ISCs, and five ISFPPs failed. Biological complications were recorded in 24.8% of TSFDPs and in 9.6% of implant-supported FDPs (p = 0.012). Technical complications were recorded in 29.9% of TSFDPs and in 27% of implant-supported FDPs (p = 0.62). Low OHIP-14 scores were reported in patients with tooth-supported (4.8 ± 6.7), implant-supported (3 ± 4.3), and with both types of FDPs (3.5 ± 3.6). Scores that indicate a good OHRQoL. Conclusion Tooth- and implant-supported FDPs had high survival rates after 5 and 10 years. Biological complications had the highest impact on prostheses failure.